Pembangunan Sistem Informasi Pemesanan Jasa Foto berbasis Web menggunakan REST API pada Heroe Photography - Eggi Tresna Faturahman; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Heroe Photography is a photo service company for weddings, pre-wedding events, and others. Heroe Photography wants to improve the quality of its services to be more competitive. But there are obstacles in existing business processes. Therefore, the solution that can be provided is a web-based photo service ordering information system using a REST API that is integrated with Midtrans as a payment gateway and Wablas as a WhatsApp gateway. Efficiency is an important factor in this research because it changes the process from previously paper-based to computer-based. Testing the validity of the black box method to test the functional requirements of the system with 100% valid test results. Performance testing with Apache JMeter tools with the result that the system can handle requests well up to 100 samples but is vulnerable if more than 200 incoming requests. Usability testing of the Nielsens Attributes of Usability (NAU) method with a result of 77.2% which states that the system is included in the category worthy. In addition, to measure the efficiency aspect, measurements are made of the time required during the ordering and payment process before and after using the system. There is an average time difference of 9.25 minutes when using the system so it can be stated that the ordering and payment processing system it becomes more efficient. This statement is also supported by the results of statistical analysis of the efficiency aspect of usability testing with a value of 4,125 which states that respondents agree if the system built fulfills the efficiency aspect.